Comprehensive Physiology 2016
DOI: 10.1002/cphy.c140049
|View full text |Cite
|
Sign up to set email alerts
|

Lung Circulation

Abstract: The circulation of the lung is unique both in volume and function. For example, it is the only organ with two circulations: the pulmonary circulation, the main function of which is gas exchange, and the bronchial circulation, a systemic vascular supply that provides oxygenated blood to the walls of the conducting airways, pulmonary arteries and veins. The pulmonary circulation accommodates the entire cardiac output, maintaining high blood flow at low intravascular arterial pressure. As compared with the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 729 publications
(821 reference statements)
3
83
0
1
Order By: Relevance
“…The phenotype observed in CH models is consistent with PH that develops in humans as a result of high altitude (reviewed in Refs. 219,228). Both rats and mice are common choices for exposure to CH.…”
Section: Models Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype observed in CH models is consistent with PH that develops in humans as a result of high altitude (reviewed in Refs. 219,228). Both rats and mice are common choices for exposure to CH.…”
Section: Models Of Phmentioning
confidence: 99%
“…Many recent investigations have focused on the role played by exogenous signaling molecules produced by inflammatory cells in driving abnormal vascular cell function in PAH (68,228,252). Hypoxia-induced mitogenic factor (HIMF, FIZZ1), a protein secreted by M2 macrophages, promotes a proinflammatory milieu in the lung vasculature.…”
Section: Pathways and Targetsmentioning
confidence: 99%
“…This is mainly as the lung is the first filter in the general circulation (3,4). Secondly, the low pressure system and slow blood flow velocities of the pulmonary circulation are apt to allow tumor cells to stagnate (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly as the lung is the first filter in the general circulation (3,4). Secondly, the low pressure system and slow blood flow velocities of the pulmonary circulation are apt to allow tumor cells to stagnate (3,4). Metastatic neoplasm often present as multiple lung nodules and masses when incidental can be detected by a diagnostic chest radiography of computed tomography (CT) scan (5).…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of pulmonary physiology in relation to gas exchange is the impact and pattern of pulmonary flow. Lower flows (especially nonpulsatile) during EVLP might result in lower vascular recruitment and simply exclude perfusion of injured regions, thereby falsely increasing P/F ratios [16,17]. Our group recently demonstrated that also the impact of flow distribution during EVLP by prone positioning might affect physiological parameters and extravascular lung water content [18].…”
mentioning
confidence: 99%